Analysis of backflow within an external centrifugal blood pump for ventricular assist device - Chitsanupong Rungsirigulnan (2018)
During left ventricular support by rotary blood pumps (RBPs), pump speed plays an important role in the amount of heart support. The reducing of pump speed seems important in order to prevent some adverse events in the heart valve. However, when pump speed was reduced, the backflow which is the flow that has the reverse direction to blood pumping direction may occur more easily. This is due to the amount of pressure at an outlet of pump. Head pressure and pump flow curve (HQ-curve) is the graph that shows the performance of speed, head pressure and flow rate in the blood pump. In this study, two impellers from MUAD-VAD02 were used; 90-degree-angle straight blade (90SB) and 130 degrees straight blade (130BSB). The backflow of two impellers were investigated at three pump speeds (1000, 1400 and 1800 rpm) using HQ-curve, negative flow rate vs. time, and pressure vs. time. The experimental study uses in vitro testing by simulating the natural circulatory system with RBPs in the mock circulation loop system. The back flow of 90SB had more negative flow than BSB at all three speeds. In conclusion, BSB- impeller was chosen over the 90SB-impeller because at the same head pressure and speed in HQ-curve, the BSB impeller has less negative flow. © 2013 IEEE.